Rethinking the Teaching-Learning Process : The 21st Century Digital Learner - Dr. Prarthita Biswas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present scenario technology in education is a very much important and challenging concept. The new ways of teaching are learning through E- Content, through Moodle or by MOOCs, E-learning, online Education, Artificial Intelligence(AI), Learning through Government Channel and Private Channels and Learning through apps. Undoubtedly there so many benefits but there are some demerits of this mode of education, as students are facing stress and immense tension. So for their Emotional well being , school should deploy a counsellor to deal with such problems and each teacher should listen and deal with such problems. The present paper focusses on the technological advancements in education in the 21st century.